Highly sensitive diode laser absorption measurements of CO2 near 1.57 μm at room temperature - Shao, Jie; Gao, Xiaoming; Zhang, Weijun; Yuan, Yiqian; Ning, Lixin; Yang, Yong; Pei, Shixing; Huang, Wei (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The absolute absorption spectrum intensities of carbon dioxide sample have been recorded with a tunable diode laser spectrometer in the spectral range 6350–6364 cm–1, which is suitable for the in situ sensing of carbon dioxide in the lower stratosphere using a commercial telecommunication -type diode laser. It was found that the typical uncertainty of experimental line intensities is about 1% compared with the values listed in the HITRAN database, which are calculated by direct numerical diagonalization (DND).
Optica Applicata, Vol. 35, 2005, nr 1, s. 49-57
Keywords: optyka; wavelength modulation; diode lasers; absorption spectroscopy